2016
DOI: 10.4172/2161-0444.1000328
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective Properties of Antioxidant Protein from Curry leaves (Murraya koenigii L.) against Oxidative Stress Induced Damage in Human Erythrocytes

Abstract: Oxidative stress induced by reactive oxygen species (ROS) cause lipid peroxidation at the human erythrocyte membrane with subsequent alterations in the ATPases function. In this study, potential cytoprotective activities of previously reported "Antioxidant Protein from Curry leaves (APC)'' in erythrocytes against reactive oxygen (ROS) species generated by pro-oxidants in vitro. The APC prevented red blood cell lysis induced by pro-oxidants; Fe: As (2:20 μmole), Hydrogen peroxide (0.2 mM), and tertiary butyl hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The stem bark extract of M. koenigii containing carbazole alkaloids and benzoisofuranone derivatives has potent antibacterial activity against Aspergillus niger , Bacillus subtilis , S. aureus , E. coli , Proteus vulgaris , and Candida albicans [24]. The antioxidant protein from curry leaves have a potent ameliorative effect of DNA damage on human erythrocytes caused by oxidative stress [25].…”
Section: Introductionmentioning
confidence: 99%
“…The stem bark extract of M. koenigii containing carbazole alkaloids and benzoisofuranone derivatives has potent antibacterial activity against Aspergillus niger , Bacillus subtilis , S. aureus , E. coli , Proteus vulgaris , and Candida albicans [24]. The antioxidant protein from curry leaves have a potent ameliorative effect of DNA damage on human erythrocytes caused by oxidative stress [25].…”
Section: Introductionmentioning
confidence: 99%
“…The elevated level of MDA, serving as a biomarker for lipid peroxidation, found in diabetic control rats is indicative of the inadequacy of antioxidant defenses in combating damage caused by ROS (reactive oxygen species), as indicated by Jelodar et al [51] . Ningappa et al [66] reported that treating diabetic rats with curry leaves can mitigate the adverse effects of oxidative stress, prevent diabetic complications and enhance the heart's mitochondrial function. This is owing to the powerful antioxidant properties of curry leaves, which are beneficial in reducing membrane damage and related activities mediated by ROS.…”
Section: The Effect Of Clp Wlp Clex and Wlex On Antioxidant Statusmentioning
confidence: 99%
“…6). The biologically active compounds such as phenolic and flavonoid compounds are main agents for the antioxidant activity they can donate hydrogen to free radicals and break the lipid oxidation chain reaction (Ningappa and Srinivas, 2008;Zahin et al, 2013;Ningappa et al, 2016). The green synthesis of ZnO nanoparticles from the source of mesophilic bacteria (E. coli) and characterized by several techniques such as UV spectroscopy, DLS, zeta potential, FTIR, XRD and SEM for conforming ZnONPs.…”
Section: Antioxidant Activity Of Mesophilic Bacteria (Ecoli) Extract Mediated Synthesized Zinc Nanoparticlesmentioning
confidence: 99%